2008 IEEE Symposium on Computers and Communications 2008
DOI: 10.1109/iscc.2008.4625636
|View full text |Cite
|
Sign up to set email alerts
|

The impact of wireless LAN security on performance of different Windows operating systems

Abstract: This paper investigates the impact of various encryption techniques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
2
15
0
1
Order By: Relevance
“…The connection between the access point and the client was wireless. The network setup was consistent with similar research shown in the past including the previous work done on 802.11g [4]. The distance between the access point and the workstations was well within two meters in-order to maintain the optimum signal strength.…”
Section: Figure1: Network Test Bedsupporting
confidence: 80%
See 2 more Smart Citations
“…The connection between the access point and the client was wireless. The network setup was consistent with similar research shown in the past including the previous work done on 802.11g [4]. The distance between the access point and the workstations was well within two meters in-order to maintain the optimum signal strength.…”
Section: Figure1: Network Test Bedsupporting
confidence: 80%
“…(d) Beacon Interval -This function indicates the variable times in which clients meet the access point, this includes send and receive packets, and synchronism [4,5]. This setting was best left at the default interval of 100ms.…”
Section: Figure1: Network Test Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…For their experiments, they used iperf. A similar work is offered in [9], showing an investigation of the impact of various encryption techniques (WEP-64, WEP-128, and WPA) on performance of wireless LANs for Windows Server 2003, Windows XP, and Windows Vista, once again using TCP and UDP as transport protocols. In this work, netperf was used as benchmarking tool.…”
mentioning
confidence: 98%
“…An anomaly is detected when some mobile hosts use a lower bitrate than others, degrading the performance of all hosts. The anomaly is analyzed theoretically, by means of simulations, and in testbeds with several performance measurements conducted with netperf 8 , tcpperf 9 , and udpperf 10 . A comparative study of the impact of wireless encryption methods over different operating systems is presented in [8].…”
mentioning
confidence: 99%